Development of Digital Comic "Putri Andam Dewi" Using Medibang - Dian Atikah; Hutagalung, Surya Masniari (Asian Journal of Applied Education (AJAE), 2024)
The purpose of this research is to create a digital comic based on the folklore "Putri Andam Dewi" and describe the results using Medibang. The creation method used involves stages described based on Richey and Klein's theory, namely planning, production, and evaluation. The research data consists of direct quotations from the folklore "Putri Andam Dewi", which is taken from the source, namely the folktale written by Bunga Rampai Cerita Folklore Tapteng. The result of this research is a digital comic titled "Putri Andam Dewi" in Germany, which consists of several pages. An evaluation of this digital comic shows that it gets an overall score of 90, signifying excellent quality.